The revolutionary Atlantic Republican visions, 1760-1830 : a documentary history - Blaufarb, Rafe 1967- (Oxford University Press, 2018)
The Enlightenment -- The strains of empire -- Origins of the American Revolution -- Winning American independence -- Origins of the French Revolution -- The French Revolution -- Toward the Haitian Revolution -- Emanicipation and independence -- The struggles for Latin American independence -- The contours of independence -- Conclusion